2011
DOI: 10.1097/jcp.0b013e318203ea0a
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety of OROS Methylphenidate in Adults With Attention-Deficit/Hyperactivity Disorder

Abstract: OROS methylphenidate, in the flexible dosage range from 36 to 108 mg/d, was well tolerated for up to 1 year in adults with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 22 publications
(21 reference statements)
9
34
2
Order By: Relevance
“…Reasons to terminate medication included side-effects such as heart palpitations, mood instability, nausea, agitation and anxiety. This is consistent with other studies on safety and tolerability (Adler et al, 2011;Bejerot et al, 2010;Buitelaar et al, 2011). Most patients experienced mild side-effects.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Reasons to terminate medication included side-effects such as heart palpitations, mood instability, nausea, agitation and anxiety. This is consistent with other studies on safety and tolerability (Adler et al, 2011;Bejerot et al, 2010;Buitelaar et al, 2011). Most patients experienced mild side-effects.…”
Section: Discussionsupporting
confidence: 93%
“…Medication dosage seemed adequate, and in line with other studies on adults (Wender et al, 2011;Adler et al, 2011;Marchant et al, 2010). As reported in a study of a younger patient population (aged 9-21 years) (Powell et al, 2011) we found variations in dosages across time and individuals, although patients with the highest dosages had the best response.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Adler et al (2009) reported that 60% of subjects entering the longterm portion of their study with dexmethylphenidate completed the study, whereas Adler et al (2011) reported that 57% of subjects entering the long-term portion of their study with OROS MPH completed 6 months of the study. Weisler et al (2009) reported that 55% of subjects entering the long-term portion of their study with lisdexamfetamine completed 12 months of the study.…”
Section: Discussionmentioning
confidence: 95%